Are We Just Numbers Under The Blue Light Of The Cyber-Sun? - Moraru, Cristina (CAP - Public Art Journal, 2023)
We live in accelerationist times (Mackay and Avanessian), when our attention is measured in numbers of clicks, while our compulsive image production and dissemination is hindering our social relations: we have 1000 friends on social media, however we feel alone. When our social relations are digitally mediated, our social connections becomes visible, and our friendship becomes measurable and searchable (Trottier and Lyon). Even if it might seem that we are having control over this situation – since we voluntarily share online content to a chosen number of friends from our networks of like-minded acquaintances – our social media bubble structures our vision, modulating visibility and invisibility in a regime that no longer needs to interpellate us (Louis Althusser) – since we voluntary provide all the necessary data – however, it needs to reconfigure our space according to what is to be seen within that space (Jacques Rancière).  The increased number of online platforms competing for our attentions jeopardize our self-validation mechanisms and compromising our freedom. The need for validation and instant gratification has made us expose our life disregarding the dangers hidden behind this new manner of shaping communities in ‘surveillance capitalism’ (Shoshana Zuboff). Especially in times of crisis, as in our current Corona-virus pandemic, we yearn for co-belonging and solidarity, but we should ask ourselves, is cyberspace a place for solidarity? In our post-political times, when normalization happens trough visualization (Irit Rogoff), are we using the right means of approaching each other, are we able to truly engage in a cyber-community, or community, in itself, is something to be feared of, as the Corona-virus? (Jean-Luc Nancy) Under the cyber-sun, visuality becomes an instrument of capitalist power, and our vision is being structured according to an increased number of commercial and political interests. Perceived as a commodity of the cyberspace, our vision is sold to different advertisers, for whom a possible correlation between our ‘surfing’ data and our activity on social media provide a deep understanding of our consumer profile (David Lyon). On the other hand, as content providers, we deliberately offer our creativity – since social media platforms are operating a total commodification of human creativity (Christian Fuchs). Even more problematic than commodifying our vision and our creativity, is exercising a multifaceted surveillance. Each time we share images, beliefs or preferences online, we are voluntarily constructing an identity – an identity to which a number of peers, or network friends, are contributing by adding complementary information. A voluntary engagement, together with a structured – and collectively constituted – identity of ourselves, could lead to a participatory surveillance. If the images that we post on social media are contributing to a participatory surveillance, while our vision and our creativity are commodified, if we are normalized trough visualization and our cyber-friends are fluid, if our cyber-reality is liquefied, our visibility and invisibility is strategically modulated, we should we ask ourselves who we are under the blue light of the cyber-sun, can we truly be ourselves in the cyberspace? Is there a real sense of community inside the cyberspace? Is there any freedom, or are we just numbers under the cyber-sun?   Key words: cyberspace, numbers, participatory surveillance, visuality, creativity, cyber-community, cyber-sun